Mushtarak Lafzhi Analysis of نظر and its Derivation in Al-Qur’an - Sandi Aryawan; Dedi Wahyudi; Muhammad Ibnu Pamungkas; Ahmed Khalid Mohammad (PPPBA, 2024)
The Qur'an is a book revealed to the Prophet Muhammad in the Arabic language. Arabic was chosen as the language of the Qur'an not only because the Prophet Muhammad was Arab, but also because Arabic has special qualities compared to other languages. According to Ibn Kathir, Arabic is the clearest, most extensive, most eloquent language, and it provides a sense of peace when spoken. Like other languages that experience the phenomenon of a word having multiple meanings, Arabic also has this feature, known as mushtarak lafzi. Mushtarak lafzi creates ambiguity in meanings, making interpretation challenging. Based on this background, this research examines the mushtarak lafzi of the word نظر in the Qur'an. The method used in studying the word نظر is descriptive with a qualitative approach. Data collection techniques include literature study, and the analysis is conducted using semiotic analysis based on Roman Jakobson's semiotic theory. The results of this research show that the word نظر has seven meanings in the Qur'an: to see, to witness, to wait, to observe, to consider, to think, and to view. Similar research has been conducted by Muhammad Ridfan in his thesis titled